Motivation and Consumers' Perception toward Purchase Decision of the Sharia Prudential Insurance Policy - Popon Srisusilawati; Zea Fauziah; Ratih Tresnati (Universitas Islam Negeri Alauddin Makassar, 2020)
Consumer behavior in the buying process begins with the purchase interest, so that it will affect consumers who will continue to change. The purpose of this study is to analyze the motivation and consumer perceptions of the prudential insurance policy purchase decision. This type of research is quantitative verification. The research method used is descriptive survey. The results of this study reveal that consumers' motivation and perceptions are in the sufficient category in influencing the decision to purchase a Sharia prudential insurance policy. Partially the motivations and perceptions of consumers each oppose the decision to purchase an Islamic insurance policy. Positively on the decision to purchase prudential sharia insurance policies.